2014
DOI: 10.7863/ultra.33.7.1143
|View full text |Cite
|
Sign up to set email alerts
|

The Endomyometrial Thickness Measurement for Abnormal Implantation Evaluation by Pelvic Sonography

Abstract: Emergency physicians, obstetrician‐gynecologists, and other medical specialists use pelvic sonography when caring for patients presenting with early pregnancy‐related symptoms. A thin endomyometrial mantle and eccentric placement of a gestational sac should raise the suspicion for an abnormally implanted pregnancy. In such cases, an interstitial ectopic pregnancy or a cornual pregnancy, two clinically distinct entities, must be considered. This article reviews the literature and guidelines on the sonographic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…If the POCUS is suggestive of an ectopic pregnancy (tubal ring, adnexal mass, pseudogestational sac, free fluid in the abdomen, endometrial mantle measuring less than 5–8 mm concerning for an interstitial pregnancy), patients should undergo urgent ultrasonography by imaging specialists and gynecology consultation [271, 272]. …”
Section: Diagnostic Applications Of Ultrasoundmentioning
confidence: 99%
“…If the POCUS is suggestive of an ectopic pregnancy (tubal ring, adnexal mass, pseudogestational sac, free fluid in the abdomen, endometrial mantle measuring less than 5–8 mm concerning for an interstitial pregnancy), patients should undergo urgent ultrasonography by imaging specialists and gynecology consultation [271, 272]. …”
Section: Diagnostic Applications Of Ultrasoundmentioning
confidence: 99%
“…Although a myometrial mantle measurement less than 5 mm and located lateral to the round ligament have been reported as two important indicators of interstitial pregnancy [ 1 , 30 ], we excluded these two image features in our diagnostic model. Similar to the results of our study, Tulandi and Al-Jaroudi argue that a thin myometrial mantle is not an important sign to distinguish the interstitial pregnancy from an eccentrically located intrauterine pregnancy [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating interstitial from angular pregnancies has proven difficult despite advances of 3D sonography and MRI. A myometrial mantle measurement of <5 mm, in addition to a gestational sac separate from the endometrium, is often denoted as indicative of an interstitial pregnancy despite low specificity [ 15 , 16 ]. However, a 2017 retrospective review of 44 interstitial and angular pregnancies found that myometrial thickness <5 mm was present in 96% of interstitial pregnancies but also 50% of angular pregnancies (range 3–8 mm) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%